STRATEGI KOMUNIKASI PEMASARAN PROGRAM PRABAYAR PT.PLN (PERSERO) DI KOTA KENDARI (STUDI PADA BAGIAN HUMAS PT.PLN AREA KENDARI) - Windy Lestari (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2016)
ABSTRACT Marketing communications is an attempt to convey a message to the public, especially the target consumer about the existence of a product or program. Marketing communications strongly support the company's marketing strategy. In 2012, PT. PLN (Persero) Area Kendari launched its newest prepaid electricity. To introduce a new program to the community particularly the PLN, and therefore there must be a marketing communication strategies in order to lay people kapada prepaid electricity. Formulation of the problem in this research is how the marketing communications strategy prepaid program PT. PLN in Kendari ?, the purpose of  While this research is to find out how the marketing department of the strategies used in marketing or public relations prepaid electricity to the people of Kendari. This study used a qualitative approach, where information or data that is collected is described by the expression and interpretation of the informants who had previously been determined by purposive sampling technique using observation, interview and documentation as data collection techniques. The reason researchers use descriptive qualitative study is to obtain data and understand the phenomena experienced by informants. In this study the researchers wanted to know how to do marketing communication strategy of public relations or marketing PLN prepaid electricity program in disseminating to the public. Researchers conducted interviews with an informant and to other informants that has researchers set. From these results, in setting and implementing marketing communications strategies prepaid program, the authority of the publicity department of Kendari Area PLN. But there are some socialization assisted by the government. The goal of segmentation in marketing communications in terms of disseminating this prepaid electricity that household customers who have electric power began 900 kwh 5500 kwh. And as a communicator of marketing communications have prepaid electricity is part of marketing and public relations. The message conveyed to the communicant between the differences between prepaid electricity with electricity postpaid, benefits, up to the cost of tokens / vouchers and purchase of electric energy used is token.Saluran communication media such as through television, radio RRI, local newspapers and internet Kendari Post Besides the usual PLN following the exhibition of public service. Key word: Strategy, Marketing Communications, Prepaid Electricity.